SENSITIVITY ANALYSIS ON THERMOHYDRAULIC CODE FOR MODIFIED PLATE-FUELED 2 MW TRIGA - Hastuti, Endiah Puji; Widodo, Surip (Urania : Jurnal Ilmiah Daur Bahan Bakar Nuklir, 2019)
SENSITIVITY ANALYSIS OF THERMOHYDRAULIC CODE FOR MODIFIED PLATE-FUELED 2 MW TRIGA. The plan to modify TRIGA 2000 Bandung from using regular TRIGA fuel to plate-type fuel should be supported by the use of appropriate computer codes. This research proposes three codes to design reactor thermohydraulics at transient condition. Analysis has been performed to identify code sensitivity using the same input and correlation. The codes used were COOLOD-N2, Heathyd, and PARET-ANL. The input was obtained from preliminary analysis of a flow rate calculation of 70 kg/s and a nominal power of 2 MW. The comparison of these three codes did not consider uncertainty factor for neutronic and technical aspects. The sensitivity analysis on thermohydraulic codes used to calculate heat transfer in the fuel plate of TRIGA reactor at steady state condition indicates similar temperature trend lines for the coolant, plate, and fuel meat. Temperature calculation results obtained from COOLOD-N2, Heathyd and PARET ANL give consistent sensitivity with the differences of coolant temperature from 2.83% to 12.5%; cladding temperature  from 2.14% to 31.30%; and fuel meat temperature  from 6.63% to 18.64%. The margins of flow instability were 5.03; 5.68 and 4.21, respectively for COOLOD-N2, Heathyd, and PARET-ANL. These values show that flow instability has not yet occurred. The results of the analysis show that the use of those three codes for steady state condition using the same input, in which uncertainty factor is neglected, give similar trend for coolant, cladding, and fuel meat temperature. As the modelling in each code is different, the values obtained are not exactly the same.Keywords: sensitivity analysis, TRIGA Plate, COOLOD-N2, Heathyd, PARET-ANL